Teaching-Learning of Mathematics through simple activities - Prakash, (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
All the individuals have unique characteristics and potentials, which if identified and nurtured can facilitate learning and get the required learning outcome. In this paper, I focus on the students who appear to be intelligent but do not learn mathematical concepts, terms, operations, reading numerical symbols, counting objects and learning multiple tables. In spite of their best efforts, these children fail to read the proficiency of their grade level in reading, writing and arithmetic. Such children are slow learners. These children can be provided special training in perception, improvement of attention and coordination of visual and motor coordination in mathematics give credit for each step, they complete correctly. I provide them concrete teaching learning experience of mathematics with the help of origami and paper cutting activities. These children require repetition and practice more than other children. Students want to escape from learning of mathematics. They assume that mathematics is only for making calculations. They are deprived from the inner beauty of mathematics. But if we relate mathematics with some hands-on activities, then they feel excited and take interest in the process of teaching learning of mathematics. ‗Learning by doing‘ gives the chance for self-learning to students and provides scope for using creative and enhance and enhance analytical and critical thinking, logical reasoning. Each class divided in groups. Each group has four to five students. Each group performed the activity and presented it to the whole class. After that, the remaining class provided suggestions for batter performance. In the present paper, researcher personally organized and implemented origami (paper folding) and paper cutting activities to enhance learning in different branches of mathematics like arithmetic, algebra and geometry. Correlated test was used for analyzing data and the results were in the favor of teaching of mathematics with the help of paper folding activities. Some sample of activities: - Visualize   20 =1, (a+b)2 = a2 +2ab + b2 and Pythagoras Theorem. Hence the present paper analyses the various activities of paper folding and paper cutting to make the learning of mathematics meaningful, realistic and life oriented. Origami activities performed by students contribute to the development of their basic mathematical concepts and get the required learning outcome.